MEP SYSTEM INSTALLATION RELATED REWORK CAUSES AND IMPACT ON PROJECT PERFORMANCE; A CASE STUDY OF RIYADH METRO PROJECT SAUDI ARABIAN - Muhammad Wajidullah Khan, Muhammad Wajidullah Khan; Muhammad Farid Shaari, Muhammad Farid Shaari; Sharafat Hussain, Sharafat Hussain (ECB, 2023)
Mechanical, Electrical and Plumbing (MEP) system is lifeblood of a building which enhances building quality and functionality. For instance, you are in the most magnificent building of a city, if the air conditioning and lights are taken away you will be left in a dark and a suffocated shell. The application of modern building services has increased installation complexities in construction projects. Consequently, rework during the installation phase has become common and acceptable practice in the construction industry. At MEP system installation phase wrong execution of any activity at the very first attempt causes quality deviations, cost overruns and time delay. The main aim of this research is to investigate occurrence of reworks in MEP installation phase and to identify their impact on project performance. This case study included three main transfer stations of Riyadh Metro Project (RMP) in Saudi Arabia. The questionnaire survey was conducted using probability sampling technique, randomly 130 experienced construction professionals (project managers, site engineers, supervisors, field engineers, quality control and project control engineers) from client, consultant, contractor and sub-contractors. The data analysis was conducted in SPSS (Statistical Package of Social Sciences) and finally, the research result revealed some potential causes of rework which impact the project performance. The causes of reworks such as; improved coordination between design and construction, allocation of qualified MEP engineers, deploying of skilled workers, use of approved design at installation stage and timely submission of inspection requests to the engineer were presented high rank by the construction experts. The research concluded potential triggers of rework as a pathway to guide MEP engineers and construction professionals to enhance performance of forthcoming building projects.